2014
DOI: 10.4238/2014.october.20.20
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of ultrafiltered XinMaiJia extract against H2O2-induced injury in human umbilical vein endothelial cells through NHE1 downregulation

Abstract: ABSTRACT. We examined the protective effects of ultrafiltered XinMaiJia (XMJ) extract in a hydrogen peroxide (H 2 O 2 )-induced injury model in human umbilical vein endothelial cells (HUVECs) and determined the corresponding changes in the Na indicators, cytokine concentration, NHE1 protein content, and NHE1 gene expression were determined. H 2 O 2 significantly promoted HUVEC injury, whereas ultrafiltered XMJ extract significantly improved the morphological changes in injured HUVECs, increased their activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…Once generated, ROS readily react with unsaturated fatty acids and cholesterol molecules present in cell membranes, thus leading to cellular apoptosis through mitochondrial pathways involving nuclear factor-κB, p53 and stress-activated protein kinase ( 41 ). In the present study, oxidative stress was investigated in HUVECs by assessing ROS production and MDA concentration; the results of which revealed that ROS and MDA levels were significantly increased following H 2 O 2 treatment, whereas cell viability was significantly reduced, thus indicating that H 2 O 2 was able to induced apoptosis in HUVECs, which is in accordance with previous studies ( 27 , 37 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Once generated, ROS readily react with unsaturated fatty acids and cholesterol molecules present in cell membranes, thus leading to cellular apoptosis through mitochondrial pathways involving nuclear factor-κB, p53 and stress-activated protein kinase ( 41 ). In the present study, oxidative stress was investigated in HUVECs by assessing ROS production and MDA concentration; the results of which revealed that ROS and MDA levels were significantly increased following H 2 O 2 treatment, whereas cell viability was significantly reduced, thus indicating that H 2 O 2 was able to induced apoptosis in HUVECs, which is in accordance with previous studies ( 27 , 37 ).…”
Section: Discussionsupporting
confidence: 90%
“…3 ). Annexin V-positive cells and cellular uptake of PI were evaluated in order to distinguish between living, apoptotic and necrotic cells, as previously described ( 37 ). The proapoptotic effects of H 2 O 2 treatment appeared to be concentration-dependent ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By using gene expression array, we identified several signaling pathways related to NO, FOXO, apoptosis, cell cycle, AMPK, MAPK, NF-kB, and PPAR, which were affected by XMJ in endothelial cells. We choose NO signaling as a candidate because NO signaling was in the pecking order among these signaling, consistent with our previous studies that XMJ produces the anti-inflammatory and antioxidant effects in HUVECs by increasing NO productions 19 26 27 . This is also highly related to clinical investigations that Chinese medicine has globally recognized to improve health conditions by activating NO signaling 28 .…”
Section: Discussionmentioning
confidence: 91%
“…Development of pathological oxidative stress injury participates in this disease. Currently, many studies have considered the H 2 O 2 -induced cell injury model as the model by which to elucidate mechanisms related to neuroinflammation and apoptosis-linked cell injury in vitro and its treatment outcomes, [42][43][44][45][46] because H 2 O 2 simulate hypoxic environments, including, ROS production and loss of MMP in neuron. Protection of DNLA against ischemia-induced injury in vivo has been reported.…”
Section: Discussionmentioning
confidence: 99%